The Influence of Technology Developments on Communication Disorder in the areas of Social and Emotional Activities - Pascal Muam MAH; Iwona SKALNA (Communications of International Proceedings, 2021)
Technology advances on communication has transferred human social and emotional interactions from physical space to social media environment. Advanced implementation and use of (ICT) tools in day’s society have expose us to social media modernity and make us forget about our physical daily interactions. With the coming of internet of things (IoTs), artificial intelligence (AI), natural language processing (NLP), emotional intelligence (EI), Robots, cloud computing, big data and social media environment, humanity have got involved in challenges or changes from the social media space which require new technology such as society 5.0.  Society 5.0 allow human interact with others and same time with technological tools. Machines have silenced the interaction between humans nowadays by taking over social and emotional attachments. Physical and emotional attachments have been shattered and deviated to emotional intelligence via video calls, text messaging, and emailing. Social interactions have been deviated to a new environment called social media environment made up of (Twitter, Facebook, WhatsApp, Viber, imo, zoom, Microsoft Teams, messenger, Gmail, text messages Instagram, TikTok). Society 5.0 technology ensure harmony and understanding of expectations that portray a course of action with little or no disruptions of social and emotional activities. Human activities will be at the center of every technological aspects that will not consume human culture any longer. The study identifies aspects of humanity disrupted by technology, suggest a suitable balance sheet of modern technology and modern humanity. It recognizes that technology has come to help ameliorate human activities but not to replace human ethical culture.
Keywords: Technology Development; Communication Influence; Social and emotional activities; Social Media environment.